Investigating the Impact of Interactive Speaking Activities on EFL Learners’ Fluency and Accuracy The Case of First-Year LMD Students of English at Souk-Ahras University. - Hadjer SAOULA (My University, 2024)
Abstract The current research seeks to investigate how using interactive speaking activities can improve the fluency and accuracy of EFL students in the language learning process. It also aims to develop their communicative skills during oral performance, helping them overcome challenges faced in EFL classes. Aiming to evaluate the primary hypotheses, this descriptive and explanatory research adopted a mixed-method approach in collecting both quantitative and qualitative data. The researcher utilized two principal instruments: a questionnaire administered to first-year LMD students at the Department of English, Souk-Ahras University, and a non-participant observation conducted during the second semester (2024) with first-year students over eight sessions during the "Oral Expression and Comprehension" course. The accumulated data elucidated that the implementation of interactive speaking activities as a pedagogical technique exerted a positive impact on Algerian EFL students' learning, proving beneficial for developing EFL learners' fluency in speaking, as they facilitated the application of theory into practice for meaningful communication during class. Nevertheless, to enhance accuracy, these activities should be complemented with focused instruction, personalized feedback, and strategies to address common language errors. ------------------------- الملخص تسعى الدراسة الحالية إلى استقصاء كيف يمكن استخدام أنشطة التحدث التفاعلية في تحسين الطلاقة والدقة لدى طلبة اللغة الإنجليزية كلغة أجنبية في عملية تعلم اللغة. كما تهدف إلى تطوير مهاراتهم التواصلية أثناء الأداء الشفوي، ومساعدتهم على التغلب على التحديات التي يواجهونها في فصول اللغة الإنجليزية كلغة أجنبية. سعياً لتقييم الفرضيات الرئيسية، اعتمدت هذه الدراسة الوصفية والتفسيرية نهجًا مختلطًا في جمع البيانات الكمية والنوعية. استخدم الباحث أداتين رئيسيتين: استبيانًا أُجري على طلبة السنة الأولى في قسم اللغة الإنجليزية بجامعة سوق اهراس ، وملاحظة غير مشاركة أجريت خلال الفصل الدراسي الثاني (2024) مع طلبة السنة الأولى على مدار ثماني جلسات خلال مقرر "التعبير والفهم الشفوي". وضحت البيانات المتراكمة أن تنفيذ أنشطة التحدث التفاعلية كأسلوب تربوي أحدث تأثيرًا إيجابيًا على تعلم طلبة اللغة الإنجليزية الجزائريين، وأثبت فائدته في تطوير طلاقة المتعلمين في التحدث، حيث سهل تطبيق النظرية إلى الممارسة للتواصل الهادف خلال الحصة. ومع ذلك، لتعزيز الدقة، يجب أن تكمل هذه الأنشطة بالتدريس المركز، والتغذية الرجعية .الشخصية، والاستراتيجيات لمعالجة الأخطاء اللغوية الشائعة -------------------- Résumé La recherche actuelle vise à examiner comment l'utilisation d'activités de conversation interactives peut améliorer l'aisance et la précision des apprenants d'anglais langue étrangère (EFL) dans le processus d'apprentissage des langues. Elle vise également à développer leurs compétences communicatives lors de leurs performances orales, les aidant à surmonter les défis rencontrés dans les cours d'anglais langue étrangère. Dans le but d'évaluer les hypothèses principales, cette recherche descriptive et explicative a adopté une approche mixte pour la collecte de données quantitatives et qualitatives. Le chercheur a utilisé deux instruments principaux : un questionnaire administré aux étudiants de première année LMD du Département d'Anglais de l'Université de Souk-Ahras, et une observation non participante menée pendant le deuxième semestre (2024) avec des étudiants de première année sur huit sessions pendant le cours "Expression et Compréhension Orales". Les données accumulées ont clarifié que la mise en œuvre d'activités de conversation interactives en tant que technique pédagogique a eu un impact positif sur l'apprentissage des étudiants algériens d'anglais langue étrangère, s'avérant bénéfique pour le développement de l'aisance à l'oral des apprenants, car elles ont facilité l'application de la théorie à la pratique pour une communication significative en classe. Néanmoins, pour améliorer la précision, ces activités devraient être complétées par un enseignement ciblé, un feedback personnalisé et des stratégies pour traiter les erreurs linguistiques courantes.